Background Paper: Research and Development and Extension Services in Agriculture and Food Security - Annie Wesley; Merle Faminow (Asian Development Bank (ADB), 2014)
Investments in agricultural research and extension have consistently demonstrated high rates of return in Asia and the Pacific. However, the recent global food crisis exposed the vulnerability of food supply systems and reversed many past achievements in the fight against hunger and malnutrition. It also demonstrated the need for continued innovation. In view of the emerging economic, climatic, and political scenarios in the region, this paper explores the role of applied research for development and extension services through the two-pronged approach of boosting food production and preventing losses. Priority areas for research emphasize attention to smallholder farming systems, practical business models, the integration of gender, and multidisciplinary research that is sensitive to nutritional outcomes. In addition, pioneering mechanisms to public-private partnerships are examined towards the strategic use of renewed stakeholder commitments to achieve food security and prevent future crisis. By learning from the past and looking into the future, this paper makes a case for sustained investments in research and extension to address the numerous challenges along the pathway from agriculture production and distribution to consumption and utilization.
hdl:11540/4220
Keywords: Q16; 330; food security; agriculture; research and extension; the Asia and Pacific region; Ernährungssicherung; Landwirtschaft; Entwicklung; Wirtschaftsordnung; Asiatisch-pazifischer Raum